2017
DOI: 10.1136/bmjopen-2017-016819
|View full text |Cite
|
Sign up to set email alerts
|

Can traditional risk factors explain the higher risk of cardiovascular disease in South Asians compared to Europeans in Norway and New Zealand? Two cohort studies

Abstract: ObjectivesThe objective was to prospectively examine potential differences in the risk of first cardiovascular disease (CVD) events between South Asians and Europeans living in Norway and New Zealand, and to investigate whether traditional risk factors could explain any differences.MethodsWe included participants (30–74 years) without prior CVD in a Norwegian (n=16 606) and a New Zealand (n=129 449) cohort. Ethnicity and cardiovascular risk factor information was linked with hospital registry data and cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…However, the Framingham score overestimated risk substantially in Indian women with predicted risk values of about 6% and above, and in European men and women in all but the two lowest deciles of predicted risk. Despite Indians being around 6–8 years younger than Europeans in the cohort, their observed 5-year CVD event rates were very similar to the observed 5-year CVD event rates in Europeans, consistent with the previously documented high burden of CVD in South Asians in New Zealand 22 and other countries. 1 23 We also found a positive association between increasing BMI (from BMI≥18.5) and the risk of CVD in both ethnic groups which remained statistically significant in all the subgroups except European women after adjustment for the Framingham risk score.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the Framingham score overestimated risk substantially in Indian women with predicted risk values of about 6% and above, and in European men and women in all but the two lowest deciles of predicted risk. Despite Indians being around 6–8 years younger than Europeans in the cohort, their observed 5-year CVD event rates were very similar to the observed 5-year CVD event rates in Europeans, consistent with the previously documented high burden of CVD in South Asians in New Zealand 22 and other countries. 1 23 We also found a positive association between increasing BMI (from BMI≥18.5) and the risk of CVD in both ethnic groups which remained statistically significant in all the subgroups except European women after adjustment for the Framingham risk score.…”
Section: Discussionsupporting
confidence: 88%
“…The UK study found that Framingham underestimated risk in South Asian women and performed reasonably well in South Asian men after a factor of 1.4 was added to the score. 26 Based on these findings, 26 the previously documented high burden of CVD in South Asians 22 and New Zealand guidelines recommendations to add 5% to the risk score for South Asians, 2 we would expect the Framingham risk score to underestimate risk among Indians in New Zealand. Instead, we found that Framingham overestimated the risk in Indian women and in Europeans of both genders.…”
Section: Discussionmentioning
confidence: 86%
“…A recent longitudinal cohort study involving individuals with low 10-year heart risk score found that trends of elevated low-density lipoprotein (LDL) and non-high-density lipoprotein (HDL) cholesterol (≥160 mg/dL) were independently associated with a 50%-80% increased relative risk of CVD mortality (Abdullah et al 2018). A comparison of risks of CVD events between SAs and Europeans from Norway who had no previous CVD events indicated that SAs had 87%-92% higher age-adjusted risk (Rabanal et al 2017). The differences in baseline total cholesterol/ LDL ratio and diabetes prevalence explained the excess CVD risk in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals of South Asian (SA) descent are either born in or can trace their ancestry to India, Pakistan, Nepal, Bangladesh, or Sri Lanka. SAs have significantly higher risk for early onset of cardiovascular diseases (CVD) (Joshi et al 2007), hyperinsulinemia, and dyslipidemia compared with other Asians and individuals of European descent (Ahmed and El-Menyar 2014;Rabanal et al 2017;Volgman et al 2018). Also, the mortality risk associated with CVD is higher in SAs compared with Europeans, Americans, other Asians (Ahmed and El-Menyar 2014), or Africans (Chaturvedi 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, immigrants and Norwegianborn to immigrant parents with a country background from South Asia living in Norway counted 75,227 individuals [12]. We previously reported that immigrants from South Asia have an increased risk of CVD compared to ethnic Norwegians after adjustment for traditional risk factors [13].…”
Section: Introductionmentioning
confidence: 99%